Práticas inclusivas e intervenção educacional: um estudo de intervenção nas salas de recursos multifuncionais nas escolas do polo Centro do município de São Luís – MA - MAIA, Ginia Kenia Machado (2020)
The research comes to the thematic: INCLUSIVE PRACTICES AND EDUCATIONAL INTERVENTION: a study in the multifunctional resource rooms in the schools in the center of the city of São Luís-MA, with the objective of accomplish educational intervention in the Multifunctional Resource Room in an inclusive perspective for students with Intellectual Disabilities with views to building a Guide to educational propositions. The research was characterized as a collaborative intervention, with the delimitation of 5 (five) schools in the center pole of the city of São Luís – MA, that have Multifunctional Resource Rooms (SRM). The research subjects were the 5 (five) teachers and 5 (five) responsible of students with Intellectual Disabilities. To forward the collaborative intervention, we followed the methodological steps for the analysis and interpretation of the semi-structured interviews directed to the subjects, our analysis was based on the theoretical and methodological axes materialized throughout the study. Collaborative interventions were realized out through classroom observations, study sessions with teachers and interviews, all this methodological path led us to produce a Guide to educational propositions. In this process of building the dissertation, mainly of the product, it was found that the teachers passed to value even more the record of the students' activities, and to intensify the possibilities of pedagogical activities/resources in the same task, through by expanding the usefulness of this resource, to develop skills and competences of the specific functions of the student with Intellectual disability. t became evident, although there are many challenges in the work of the Multifunctional Resource Room with DI students, however, it is noticeable through the speeches of those responsible for the recognition and appreciation of these professionals. In the interviews with the teachers, the longings and needs for pedagogical monitoring of the work being carried out were perceived, as well as the challenge of dealing with the specificities present in the MRR. In summary, with the proposal of the final product thought it was possible to contribute to the practices of teachers and the expansion of methodological possibilities to work with students with ID in the local reality considering their needs and singularities.